2019
DOI: 10.1080/1177083x.2019.1640752
|View full text |Cite
|
Sign up to set email alerts
|

The geographic distribution of gaming machine proceeds in New Zealand

Abstract: Within NZ gambling and its associated harms are well-researched topics. However, most studies to date have relied upon the use of survey methodology or have focused on individual regions. In this paper we distribute gaming machine proceeds (GMP) from gaming venues to the surrounding localities in order to derive estimates of GMP per capita. It is hoped these estimates will enable the trusts who operate the electronic gaming machines (EGMs), and who are responsible for reinvesting a proportion of proceeds back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…7 There is a gradient of harm from the use of EGMs which aligns with socioeconomic status (SES), with lower SES correlated with increased harm. 8 Pokies are more densely concentrated in low socioeconomic regions; this aligns with the evidence showing that proximity to EGM venues is a risk factor for problem gambling. 8 Māori are more likely to be affected by gambling-related harm than non-Māori due to increased exposure in communities where Māori are more likely to live, and the correlation with other factors which predispose to harmful gambling such as poverty, other addictions, and job insecurity.…”
Section: Gambling-related Harmsupporting
confidence: 81%
See 2 more Smart Citations
“…7 There is a gradient of harm from the use of EGMs which aligns with socioeconomic status (SES), with lower SES correlated with increased harm. 8 Pokies are more densely concentrated in low socioeconomic regions; this aligns with the evidence showing that proximity to EGM venues is a risk factor for problem gambling. 8 Māori are more likely to be affected by gambling-related harm than non-Māori due to increased exposure in communities where Māori are more likely to live, and the correlation with other factors which predispose to harmful gambling such as poverty, other addictions, and job insecurity.…”
Section: Gambling-related Harmsupporting
confidence: 81%
“…8 Pokies are more densely concentrated in low socioeconomic regions; this aligns with the evidence showing that proximity to EGM venues is a risk factor for problem gambling. 8 Māori are more likely to be affected by gambling-related harm than non-Māori due to increased exposure in communities where Māori are more likely to live, and the correlation with other factors which predispose to harmful gambling such as poverty, other addictions, and job insecurity. 9 The Alert Level 4 lockdown was a snapshot of what our communities could look like without pokies.…”
Section: Gambling-related Harmsupporting
confidence: 81%
See 1 more Smart Citation
“…Recent research from New Zealand has distributed proceeds from EGMs to the surrounding areas using inverse Huffmodelling to establish measures of EGM proceeds per capita at area level. It was found that the levels of EGM proceeds were highest in areas with the highest levels of socio-economic deprivation (Ward et al, 2020).…”
Section: Egm Density Socio-economic Status and Gambling Related Harmsmentioning
confidence: 99%
“…As colourism could be related to Paula's experience, migrant research discusses exclusionary behaviour against migrants. This kind of discriminatory behaviour is often referred to in the literature as the negative context of reception (Ward et al, 2019). When 76 migrants do not perceive their host country environments as welcoming and appreciative of other cultures, this can be related to negative health outcomes such as poor mental health and wellbeing (Ward et al, 2019).…”
Section: Racism and Discrimination Experiencesmentioning
confidence: 99%